Forget the toad and eat the frog: no associational protection against fish from a chemically defended toad to a later-breeding anuran species. Issue 4 (4th July 2022) - Kaczmarek, Jan M.; Kaczmarski, Mikołaj; Mazurkiewicz, Jan; Kloskowski, Janusz
Abstract : Associational effects such as "associational resistance" or "aposematic commensalism" may facilitate the subsequent evolution of mimicry. However, such effects are usually expected to be contingent on a spatiotemporal co-occurrence of defended and undefended species. Associational resistance may emerge in communities of larval anurans where tadpoles of different species share a generalized morphology but vary in chemical defences. In Europe, the marsh frog Pelophylax ridibundus reproduces in fish-containing habitats that earlier in the season can be used by the common toad Bufo bufo, a species with chemically defended larvae. In a mesocosm experiment, we investigated if the associational protection against predation provided by the defended species could be strong enough to last even after the defended prey metamorphose and leave the system. We expected that the higher abundances (both absolute and relative) of chemically defended B. bufo in the tadpole assemblage exposed to predation by the common carp Cyprinus carpio prior to the occurrence of P. ridibundus tadpoles would be related to the increased later survival of P. ridibundus in the presence of the same fish. The tadpoles of P. ridibundus were highly vulnerable to predation during a 2-week cohabitation with fish. We found no relationship between the survival of P. ridibundus and the absolute density or relative proportion of B. bufo . Although associational effects may be ecologically relevant in aquatic animal communities, they apparently require the co-presence of the defended prey in fish-tadpole interactions.